Helicobacter pylori Subdues Cytokine Signaling to Alter Mucosal Inflammation via Hypermethylation of Suppressor of Cytokine Signaling 1 Gene During Gastric Carcinogenesis - Jan, Iqra; Rather, Rafiq A.; Mushtaq, Ifra; Malik, Ajaz A.; Besina, Syed; Baba, Abdul Basit; Farooq, Muzamil; Yousuf, Tahira; Rah, Bilal; Afroze, Dil (Frontiers in Oncology, 2021)
Helicobacter pylori (H. pylori) infection has been associated with the onset of gastric mucosal inflammation and is known to perturb the balance between T-regulatory (Treg) and T-helper 17 (Th17) cells which causes a spurt of interleukin 17 (IL17) and transforming growth factor-β (TGF-β) from Th17 and Treg cells within the gastric milieu. IL17 instigates a surge of interleukin 6 (IL6) from T-helper 1 (Th1) and T-helper 2 (Th2) cells. Further, H. pylori infection is known to stimulate the atypical DNA methylation in gastric mucosa. However, the precise role of cytokine signaling in induction of epigenetic modifications during gastric carcinogenesis is vaguely understood. In this study, patient samples from were examined using real-time polymerase chain reaction (qPCR), PCR, methylation-specific (MS)-PCR, and enzyme-linked immunosorbent assays. We found that H. pylori-infection augments the production of interleukin 10 (IL10), IL6, and TGF-β in the gastric milieu and systemic circulation. Together with the IL6/IL10 mediated hyperactivation of the JAK/STAT pathway, H. pylori infection causes the inactivation of suppressor of cytokine signaling 1 (SOCS1) gene through the hypermethylation of the promoter region. This study signifies that H. pylori-mediated epigenetic silencing of SOCS1 in concert with inflammatory cytokines miffs hyperactivation of the JAK/STAT cascade during gastric carcinogenesis.